(untitled) (KYAMC Journal, 2019)
Background: Blood group is one of the major genetic risk factors for developing different types of malignancy throughout the world. Objectives: To find out the susceptible blood group in ABO and Rhesus systems in patients with malignancy. Methods and Materials: This study was one at KYAMCH cancer center, Enayetpur, Sirajganj, from October 2018 to February 2019. Total 150 cancer patients attending OPD were included irrespective of age, sex, socioeconomic status. ABO and Rhesus blood groups were determined in laboratory by standard methods. Results: Among 150 patients, 55% were female and 45% were male. Malignancy was predominant in the age group of41-50 years (25.3%) and 33.33% patients were found to have O blood group. Out of the patients, 98.7% had Rh positive of all blood groups of which 32% was belonged to blood group O. Metastasis was found among 34.66% patients and out of this 14.67% were having O blood group. Among 22 metastatic O blood group patients, 90.9% was Rh positive and 9.09% was Rh negative. Conclusion: Various types of malignancy are common among O positive blood group. KYAMC Journal Vol. 10, No.-3, October 2019, Page 133-136